PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP MINAT BELAJAR DAN HASIL BELAJAR IPAS SISWA KELAS V SD - Wita Thalya Manalu; Treny Hera; Hendri Gunawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether there is an Influence of the Use of Audio Visual Media on the Interest in Learning and Learning Outcomes of Grade V Elementary School Students. This study uses an experimental method of the Posttest Control Design type. The population of this study were all grade V students of Elementary School 92 Palembang. The sample used was Saturated Sampling. Data collection techniques used questionnaires and tests. The data analysis technique used was the Mnaova Test, which was previously tested for prerequisites, namely normality and homogeneity. The results of this study showed the results of the Manova Test of the questionnaire on learning interest and learning outcomes obtained Sig. of 0.000. 0.000 <0.05 then H_o is rejected and H_a is accepted, meaning Based on the results of the study, it can be concluded that there is an influence of the use of audio visual media on the interest in learning and the learning outcomes of grade V students of Elementary School 92 Palembang. So it can be concluded that this study has an influence on students' interests and learning outcomes.